Comparison of cycloplegic refraction in children with different iris colour categories. A cross- sectional survey - Aisha Arooj; Qazi Muhammad Omair; Shazia Bano (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the cycloplegic refraction in children with different iris colour categories and age groups. Methods: The cross-sectional study was conducted from December 2022 to June 2023 at the Eye Clinic of Sehat Medical Complex, Hanjarwal, Lahore, and Khizar Eye Centre, Lahore, Pakistan, and comprised hyperopic children aged 5-12 years of either gender. Data regarding age, gender, iris colour, auto-refraction and retinoscopy before and after cycloplegic refraction was collected using a structured proforma. Data was analysed using SPSS 21. Results: Of the 139 subjects, 73(52.5%) were males and 60(47.5%) were females. There were 79(56.8%) subjects aged 5-8 years and 60(43.2%) aged 9-12 years. The iris colour distribution was 23(16.5%) light, 80(57.6%) medium and 36(25.9%) dark, with a mean visual acuity of 0.7±0.6. There was a significant difference in non-cycloplegic and cycloplegic refraction for different iris colours and age groups (p<0.05). Conclusion: Children with light iris colour accommodated more and needed a low concentration of cyclopentolate compared to those with medium and dark iris colours. More accommodation was noted among children aged 9-12 years. Key Words: Cycloplegic refraction, Cyclopentolate, Hyperopia, Iris, Ocular refraction, Retinoscopy.